To Evaluate the Outcome of Capsuloligamentaxsis and Percutaneous Fixation of Schatzkar’s Type V and VI Tibial Condyle Fractures by Multiple K-Wires (Medical Forum Monthly, 2020)
Objective: To evaluate the results when we are using percutaneous K-wires with pop cast in Schazkar’s type V and type VI fractures under image intensifier under traction. Our hypothesis is by this method we can achieved good results with minimum complication.Study Design: Descriptive case series study.Place and Duration of Study: This study was conducted at the Mayo hospital Lahore from February 2018 to March 2019.Materials and Methods: Total patients were 14 with 10 males and 4 were females. 31.4 years was the mean age of all patients and it ranges between29 to 50 years. (range;20 to 50). Schatzkar’s type V and VI fractures were fixed by multiples per cutaneous closed K –wires and pop cast applied.Results: Union occurred in all fractures. The follow up was of 24 weeks and range was from 19 to 31 weeks. Average flexion was of 115 degrees and the range was between 90 to 125 degree of the patients, the extension lag was about 5 to 10 degree in three patients. Full weigh bearing started after 15 weeks and the range of weigh bearing was from 12 to 24 weeks in all patients. there was no remarkable complication in the study. All data about pain, range of motion, flexion contracture and extension lag, valgus and Varus alignment and stability was collected. The final assessment was done with the help of KSS (Knee Society Score) criteria [16,17]. Excellent (KSS > 80) were in 4(28.57%), good (KSS 70-79) were in 5 (35.71%), fair (KSS 60-69) were in 3 (21.42%) and poor (KSS < 60) were noted in 1 (7.14%) patient.Conclusion: Fixation of fracture Percutaneously by multiple wires is treatment of choice in Schatzkar’s type V and VI with union, good range of motion and without any remarkable complication.